2020
DOI: 10.3389/fphar.2020.00507
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Melanogenic Effect of Dendropanax morbiferus and Its Active Components via Protein Kinase A/Cyclic Adenosine Monophosphate-Responsive Binding Protein- and p38 Mitogen-Activated Protein Kinase-Mediated Microphthalmia−Associated Transcription Factor Downregulation

Abstract: Dendropanax morbiferus H. Lev has been reported to have some pharmacologic activities and also interested in functional cosmetics. We found that the water extract of D. morbiferus leaves significantly inhibited tyrosinase activity and melanin formation in amelanocyte stimulating hormone (MSH)-induced B16-F10 cells. D. morbiferus reduced melanogenesis-related protein levels, such as microphthalmia−associated transcription factor (MITF), TRP-1, and TRP-2, without any cytotoxicity. Two active ingredients of D. mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Furthermore, our results indicated that KC extracts show the above-mentioned effects by promoting antioxidant activity. Melanogenesis is often observed after UV irradiation and is primarily associated with pigmentation or hyperpigmentation [ 39 ]. According to previous studies, the method of inducing melanogenesis using α-MSH has been widely recognized and applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our results indicated that KC extracts show the above-mentioned effects by promoting antioxidant activity. Melanogenesis is often observed after UV irradiation and is primarily associated with pigmentation or hyperpigmentation [ 39 ]. According to previous studies, the method of inducing melanogenesis using α-MSH has been widely recognized and applied.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the method of inducing melanogenesis using α-MSH has been widely recognized and applied. Therefore, this study was based on the construction of a melanocyte model stimulated with α-MSH [ 24 , 39 ]. We found that KC extracts suppressed α-MSH-stimulated intracellular melanin content and tyrosinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…α-MSH stimulates G protein-coupled activation of adenylate cyclase, leading to the accumulation of intracellular cAMP levels resulting in an increased level of binding to the regulatory subunit of PKA ( 49 ). Previous studies have shown that the method of inducing melanogenesis using α-MSH has been widely accepted and applied ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosinase, TRP-1 and TRP-2 are essential processes in melanogenesis regulated by MITF expression. PKA and CREB have attracted increasing research interest and are considered to be potential therapeutic targets for melanogenesis ( 24 , 49 , 50 ). Thus, the effects of PKA/CREB-modulating compounds observed during in vivo and in vitro studies are likely to be a combination of other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Several intrinsic and extrinsic factors involved in skin pigmentation have been identified. The key enzyme that regulates melanogenesis is tyrosinase, and it acts with tyrosinase-related protein 1 (TRP-1) and tyrosinase-related protein 2 (TRP-2) to promote melanogenesis (Park et al, 2020). Microphthalmia-associated transcription factor (MITF), a key activator of the tyrosinase promoter, is a master transcription factor that activates the transcription of pigmentation genes and is required for melanocyte proliferation and survival (Lee et al, 2013;Lv et al, 2020), whereas kinesin family member 5b (KIF5b) functions as a motor that regulates outward melanosome transport along microtubules (Hara et al, 2000;Hirokawa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%